2014
DOI: 10.1016/j.jpor.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Factor analyses of the Oral Health Impact Profile – Overview and studied population

Abstract: Purpose A desideratum of oral health-related quality of life (OHRQoL) instruments - such as the Oral Health Impact Profile (OHIP) - is that they accurately reflect the structure of the measured construct(s). With this goal in mind, the Dimensions of Oral Health-Related Quality of Life (DOQ) Project was proposed to investigate the number and nature of OHRQoL dimensions measured by OHIP. In this report, we describe our aggregate data set for the factor analyses in the project, which consists of responses to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 30 publications
2
77
0
2
Order By: Relevance
“…The need for patient-based data on esthetics has led to the development of specific instruments like the Oral Aesthetic Subjective Impact Scale (OASIS) [27], the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) [23], or the Orofacial Esthetic Scale (OES) [24]. At the same time, esthetics is an important component of OHRQoL [19,20] and should thus be measurable via established OHRQoL instruments. In adults, one of the most extensively investigated and most widely used instrument of this type is the Oral Health Impact Profile (OHIP) [41].…”
Section: Schlüsselwörtermentioning
confidence: 99%
See 3 more Smart Citations
“…The need for patient-based data on esthetics has led to the development of specific instruments like the Oral Aesthetic Subjective Impact Scale (OASIS) [27], the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) [23], or the Orofacial Esthetic Scale (OES) [24]. At the same time, esthetics is an important component of OHRQoL [19,20] and should thus be measurable via established OHRQoL instruments. In adults, one of the most extensively investigated and most widely used instrument of this type is the Oral Health Impact Profile (OHIP) [41].…”
Section: Schlüsselwörtermentioning
confidence: 99%
“…Die Notwendigkeit der Erfassbarkeit der vom Patienten wahrgenommenen Ästhetik hat zur Entwicklung spezifischer Instrumente geführt, wie der OASIS (Oral Aesthetic Subjective Impact Scale) [27], dem PIDAQ (Psychosocial Impact of Dental Aesthetics Questionnaire) [23] und der OES (Orofacial Esthetic Scale) [24]. Gleichzeitig ist die Ästhetik eine wichtige Komponente der mundgesundheitsbezogenen Lebensqualität insgesamt [19,20] …”
Section: Study Design and Subjectsunclassified
See 2 more Smart Citations
“…7 Recent research revealed that the OHIP covers the four main domains of OHRQoL, namely Oral Function, Orofacial Pain, Orofacial Appearance, and Psychosocial Impact. [8][9][10] The most widely used and methodologically best investigated OHRQoL instrument, [11][12][13][14][15][16][17] the OHIP provides both norms 18,19 and minimal important differences, 1,20 allowing the researcher and clinician to rate not only the clinical significance of studies' findings but also to compare those findings across many different populations.…”
mentioning
confidence: 99%